PENGARUH PDRB (PRODUK DOMESTIK REGIONAL BRUTO) PERKAPITA DAN INFLASI TERHADAP PENJUALAN OTOMOTIF DI INDONESIA - Akhmad Syari’udin (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
The development of autmotive Indonesia has a fairly rapid development so that manyinvestors who do investment in the field of automotive in Indonesia. The development ofautomotive market in Indonesia is not only influenced by internal factors, but also influenced byexternal factors, both macro variable and micro variable. One of the macro variables affectingautomotive development in Indonesia is the per capita GDP and the inflation rate of eachautomotive market region. This study aims to analyze the influence of per capita GDP andinflation rate on automotive sales based on 33 provinces in Indonesia. The methodology used isthe regression of panel data with 33 provinces cross section and time series data in 2016.The results showed that: per capita GRDP per statistically and partially significantinfluence of automotive sales in 33 provinces of Indonesia while variable inflation rate is notsignificant at confidence level95%. Whereas at 95% level of confidence, both variablessignificantly affect automotive sales in Indonesia. In other word, is simultaneously, both the percapita GDP and inflation rate variables significantly influence automotive sales in 33 provincesofIndonesia. Thus, the automotive industry needs to pay attention to these two variables indeveloping its production sales and developing the market in 33 provinces of Indonesia. TheGovernment of Indonesia, in doing the development of infrastructure should consider the growthof automotive sales in every province in Indonesia.Keywords: PDRB Percapita, Inflation Rate, Panel Data, Automotive Sales